“El valor de la autoestima en el proceso de enseñanza - aprendizaje” - Mena Gallo, Ana Karolina (2023)
This research is based on the importance of self-esteem in the daily life of human beings and the value that it has within the teaching-learning process, so it aims to determine the influence of the value of self-esteem in the process of teaching learning of the seventh year of Basic Education of the EDUCATIONAL UNIT FAE Nº5 of the Canton Latacunga, province of Cotopaxi, epistemologically it is based on the Humanistic Theory, which affects the self-concept and self-learning of students, in order to be entities capable of developing cognitively and making appropriate decisions for a harmonious coexistence based on motivation and innovation, in addition, the quantitative-qualitative approach was used and the techniques of interview and survey were worked, as a substantial part of the research, the self-esteem, characteristics, levels, self-esteem of the teacher, student, low performance and strategies to raise self- esteem are conceptualized, which guarantees the theoretical foundation of this research project, It was addressed to teachers, boys and girls of the Seventh Year of Basic General Education who became the population and study group. The guide of methodological games to improve children's self-esteem was also analyzed as a viable resource to improve school performance and at the same time facilitate the roles of teachers and students in the pedagogical process.